Wanprestasi dan Ganti Rugi dalam Transaksi Jual Beli Tiket Konser Coldplay Oleh Penjual Jasa Titip - Yurida Nariswari; Eko Rial Nugroho (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to examine and analyze the form of default carried out by ticket purchasing services and the compensation given for the default that has been. This study uses a normative legal research type, the data sources used in this study are secondary data and collect data using Literature Study and Document Study, data is analyzed using qualitative descriptive data analysis methods. The results of the study obtained are that the actions of the Coldplay concert ticket purchasing service are defaults and are included in the form of defaults not performing any performance at all. Buyers who have clearly suffered losses have the right to receive compensation, in this case the compensation given by the concert ticket purchasing service is in the form of fulfillment of performance accompanied by the provision of compensation.